Keefektifan Flexible Learning dalam Menumbuhkan Self-Regulated Learning dan Hasil Belajar Mahasiswa PGSD - - Mawardi (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2020)
Online learning using the Flexible Learning (Flearn) Learning Management System (LMS) at SWCU has been running for 17 years. To ensure Flearn's effectiveness, empirical evidence is needed, so this study aims to: 1) determine whether the level of student Self-regulated Learning (SRL) in learning using Flearn is higher than learning using Google Classrom (GC), and 2) knowing whether the level of learning outcomes mediated by the student's SRL level were higher than learning using GC. The type of research used to determine the attainment of this goal is the type of experiment using the Matching-only model Pretest-posttest Control Group design and Factorial design. Participants in this experiment involved 74 people, with details of 36 students and 1 lecturer as the 1st experimental group and 36 students and 1 lecturer as the control group (experiment 2). The experimental group 1 used Flearn, while the experimental group 2 used GC. The research instrument used test questions to measure student learning outcomes variables and SRL scale rubric to measure students' SRL level. The data analysis technique used the Independent Sample t-Test and ANCOVA technique. The results showed the following findings: 1) the level of student SRL in learning using Flearn was significantly higher than learning using GC, 2) the level of student learning outcomes mediated by the student SRL level was significantly higher than learning using GC.